Customized piezoresistive microprobes for combined imaging of topography and mechanical properties. (June 2021) - Fahrbach, Michael; Friedrich, Sebastian; Behle, Heinrich; Xu, Min; Cappella, Brunero; Brand, Uwe; Peiner, Erwin
Abstract: Customized piezoresistive cantilever microprobes with a deflection range of 120 ​μm and silicon tips of 100 ​μm height were operated in a Cypher AFM showing their functionality for measuring topography together with viscoelastic properties of thin films. For drop-in mounting in the AFM a holder was developed comprising the piezoresistive microprobe and its voltage-supply and signal-conditioning electronics. With the probe tip in contact to a glass sample we found a vertical resolution of 2.8 ​nm in a bandwidth of 1 ​kHz, which is close to the theoretical limit of 3.0 ​nm ​at a deflection of 2.5 ​μm. This resolution could be verified in topographic images of a scratch of approximately 300 ​nm in depth. Force-volume images with lithographically patterned photoresist (AZ 5214E) of approximately 300 ​nm thickness on silicon revealed contrast of the resist-covered and bare regions in topography, stiffness and adhesion. With contact-resonance imaging using the Dual AC Resonance Tracking (DART) method, patterned AZ 5214E photoresist of approximately 50 ​nm thickness could be distinguished from the bare silicon in topography, contact stiffness (indicated by contact resonance frequency shift) and adhesion (indicated by phase shift). Finally, a droplet of lubricant (Lupranol VP 9209) on glass could be detected by force volume imaging revealing a thickness of approximately 90 ​nm of the liquid layer with a sharp lateral limitation, which was clearly detected. We conclude that the piezoresistive silicon microprobe is a promising tool for emerging tasks of industrial surface metrology on manufacturing machines, including micro-finish of work pieces and elasticity, thickness, adhesion, etc. of thin solid or liquid deposits on top.